ANALISIS PROSES PEMBINAAN TAHAP AWAL NARAPIDANA PEREMPUAN di LEMBAGA PEMASYARAKATAN KELAS IIB KUPANG - Dewi, Nataly; Rabawati, Dwytias (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
This research is entitled Initial Stage Development Process for Female Prisoners at the Class IIB Kupang Penitentiary. The aim of this writing is to understand the guidance process undertaken by female prisoners, as well as analyzing various factors that influence the effectiveness of this guidance. This research uses interview, documentation and observation methods to collect primary and secondary data related to the coaching process. The research results show that there are 73 prisoners in the Kupang Class IIB Women's Prison, with 26 of them being in the initial stages of development. The coaching process begins with reception, registration and placement of prisoners, as well as introduction to the environment. Obstacles faced include a lack of facilities and infrastructure as well as excess capacity. It is hoped that this writing will provide insight into the development of more effective coaching programs, as well as increase public awareness regarding the importance of reintegrating prisoners into society.